Privacy, Surveillance, and Constitutional Rights in the Digital State - Marudut Hasugian; Noviya, Anis (PT. Anagata Sembagi Education, 2026)
The transformation of Indonesia into a digital state has intensified the use of digital surveillance technologies, including big data analytics, biometric systems, and algorithmic monitoring, in the name of public administration, security, and governance efficiency. While these developments promise administrative effectiveness, they simultaneously pose serious constitutional challenges to the protection of privacy as a fundamental right. This article examines the normative position of privacy within Indonesia’s constitutional framework and analyzes the problem of normative ambiguity surrounding state surveillance in the digital era. Employing normative juridical research with statute, conceptual, and case approaches, this study identifies the absence of clear constitutional limits on surveillance authority, vague standards for public interest and national security justifications, and weak mechanisms of accountability and oversight. The findings demonstrate that such ambiguity risks legitimizing an over-surveillance state and undermines legal certainty and substantive constitutional protection. This article argues that privacy in the digital state must be reconstructed as a core constitutional safeguard through clear legal bases, proportionality requirements, mandatory judicial authorization, and independent supervisory mechanisms, ensuring a balanced relationship between state power and fundamental rights.